Physicochemical Characteristics of Phospholipid Vesicles for Spirulina-Based Dietary Supplement Delivery - Massimo Milia; Ines Castangia; Francesco Corrias; Matteo Aroffu; Mattia Casula; Maria Letizia Manca; Maria Manconi; Hamza Bouakline; Alberto Angioni (Molecules)
Spirulina (Arthrospira platensis) is a microalga widely used as a dietary supplement in sports nutrition and in treating metabolic diseases such as diabetes, obesity and metabolic syndrome. Spirulina’s cell structure limits digestibility and reduces the availability of bioactive compounds. The extraction processes, coupled with encapsulation, can enhance the bioavailability of nutritional and antioxidant compounds, protecting them from degradation, preserving their functional activity, and supporting controlled release. The physicochemical properties of liposomes (Lps), bilosomes (Bls), and gelatin-enriched bilosomes (G-Bls) with incorporated Spirulina extracts were investigated. The delivery systems exhibited small particle size (101.8 ± 0.5 to 129.7 ± 1.2 nm), homogeneous distribution (polydispersity index (PDI) 0.17 ± 6.67 to 0.33 ± 9.06), negative surface charges (−31.9 ± 5.2 to 31.1 ± 6.4 mV), and high entrapment efficiency (>80%). G-Bls demonstrated effective retention of the extract, with a low release rate at pH 1.2 (41.8% ± 6.1) and controlled release at pH 7.0 (52.5% ± 3.0). Biocompatibility studies on Caco-2 cells showed that G-Bls maintained high cell viability at 200 μg·mL−1 (87.89% ± 10.35) and significantly mitigated H2O2-induced oxidative stress at 20 and 200 μg·mL−1, increasing cell viability by 23.47% and 19.28%. G-Bls are a promising delivery system for enhancing the stability, bioavailability, and protective effects of Spirulina extracts, supporting their potential application in dietary supplements aimed at promoting sports performance and recovery, mitigating exercise-induced oxidative stress, and managing metabolic disorders.